Reconstruction of Castration Sanction Formulation in The Perspective of Indonesian Criminal Law Renewal - Yaris Adhial Fajrin; ach faisol triwijaya (Jurnal Dinamika Hukum, 2019)
The development of crimes should be balanced by the development of criminal law-oriented policies protecting society. The castration sanction policy as a government reaction on the rise of sexual violence against children has a negative side in its establishment. The research method used in this research was normative juridical research that examined the rules or norms in positive law to find the truth based on the legal scholarly logic of the normative side. The results of research obtained were, firstly, the existence of the castration sanction based on ius constitutum did not reflect the essence of punishment so that the offenders repented, and it only aimed to arrest the offender and focused on the dehumanization potential of the offenders. Since the reality of sex crime in Indonesia was seen as an alarming phenomenon, the existence of this castration sanction was not immediately abolished from the criminal law of Indonesia in the future. Secondly, the existence of the castration sanction is still needed as long as it is positioned as a specific action and alternative to aggravated sex offenders.Keywords: Castration, Crime, Criminal law renewal, Criminal law.